2015
DOI: 10.1097/gox.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Washes and Centrifugation on the Efficacy of Lipofilling With or Without Local Anesthetic

Abstract: Background:Among the different parameters that influence fat graft survival and lipofilling success, the use of local anesthetic and the way to process the fat before injection have often been pointed out. Likewise, we evaluated different techniques for processing adipose tissue before its injection and analyzed the quality of the grafts.Methods:Adipose tissue from the same patient was gently harvested from one side of the abdomen after infiltration of a tumescent solution without lidocaine and from the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…After removing the subnatant liquid, 25 mL of harvested tissue was transferred into a 50-mL tube, rinsed with 25 mL of Ringer lactate, then centrifuged (100 g for 1 second); this step was repeated twice, followed by a final wash and a soft centrifugation (400 g for 1 minute). 11 After each step, the oil supernatant and the lower liquid phase were discarded and ultimately only the intermediate layer, which potentially contained both adipose-derived stem cells and adipose tissue-derived stromal vascular fraction, 8 was transferred into 2-mL syringes. Aspiration of joint fluid from the elected joint confirmed proper needle placement (21-gauge needle).…”
Section: Adipose Tissue Collection Processing and Injectionmentioning
confidence: 99%
“…After removing the subnatant liquid, 25 mL of harvested tissue was transferred into a 50-mL tube, rinsed with 25 mL of Ringer lactate, then centrifuged (100 g for 1 second); this step was repeated twice, followed by a final wash and a soft centrifugation (400 g for 1 minute). 11 After each step, the oil supernatant and the lower liquid phase were discarded and ultimately only the intermediate layer, which potentially contained both adipose-derived stem cells and adipose tissue-derived stromal vascular fraction, 8 was transferred into 2-mL syringes. Aspiration of joint fluid from the elected joint confirmed proper needle placement (21-gauge needle).…”
Section: Adipose Tissue Collection Processing and Injectionmentioning
confidence: 99%
“…But even if only mechanical treatments are considered, the various processing methods have a different impact on the integrity of the tissue, both in terms of cellular content and viability before and after processing. There are numerous papers in the literature that compare different processing techniques (Ansorge et al, 2014;Botti, Pascali, Botti, Bodog, & Cervelli, 2011;Butterwick, 2002;Canizares et al, 2017;Condé-Green, de Amorim, & Pitanguy, 2010;Condé-Green et al, 2013;Fisher et al, 2013;Girard et al, 2015;Hivernaud et al, 2017;Hoareau et al, 2013;Khater, Atanassova, Anastassov, Pellerin, & Martinot-Duquennoy, 2009;Mashiko et al, 2017;Minn, Min, Chang, Kim, & Heo, 2010;Palumbo et al, 2015;Pfaff, Wu, Zellner, & Steinbacher, 2014;Ramon et al, 2005;Rohrich, Sorokin, & Brown, 2004;Rose et al, 2006;Salinas et al, 2014;Smith et al, 2006;Zhu et al, 2013), but we have not found feedback for the mincing and pureeing procedures. It should be added that the same methods can be different according to the way they are used by the operators and/or implemented in the processing devices.…”
Section: Discussionmentioning
confidence: 73%
“…Coleman technique remains the gold standard for liposuction and lipofilling, but several studies have investigated the possibility to modify centrifugation parameters, in particular, reducing speed, because even the centrifuging technique is not always considered a minimal tissue manipulation technique. In fact, an excessive magnitude of centrifugal force can cause the rupture of the superficial fragile adipocytes and a loss of viability of ASCs (Bellini et al, 2017;Canizares et al, 2017;Coleman & Katzel, 2015;Galiè, Pignatti, Scambi, Sbarbati, & Rigotti, 2008;Girard et al, 2015;Palumbo et al, 2015;Strong et al, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations